A cool and inflated progenitor candidate for the Type Ib supernova 2019yvr at 2.6 yr before explosion. Issue 2 (30th March 2021) - Kilpatrick, Charles D; Drout, Maria R; Auchettl, Katie; Dimitriadis, Georgios; Foley, Ryan J; Jones, David O; DeMarchi, Lindsay; French, K Decker; Gall, Christa; Hjorth, Jens; Jacobson-Galán, Wynn V; Margutti, Raffaella; et al.
ABSTRACT: We present Hubble Space Telescope imaging of a pre-explosion counterpart to SN 2019yvr obtained 2.6 yr before its explosion as a type Ib supernova (SN Ib). Aligning to a post-explosion Gemini-S/GSAOI image, we demonstrate that there is a single source consistent with being the SN 2019yvr progenitor system, the second SN Ib progenitor candidate after iPTF13bvn. We also analysed pre-explosion Spitzer /Infrared Array Camera (IRAC) imaging, but we do not detect any counterparts at the SN location. SN 2019yvr was highly reddened, and comparing its spectra and photometry to those of other, less extinguished SNe Ib we derive $E(B-V)=0.51\substack{+0.27\\ -0.16}$  mag for SN 2019yvr. Correcting photometry of the pre-explosion source for dust reddening, we determine that this source is consistent with a log ( L /L⊙ ) = 5.3 ± 0.2 and $T_{\mathrm{eff}} = 6800\substack{+400\\ -200}$  K star. This relatively cool photospheric temperature implies a radius of 320$\substack{+30\\ -50}~\mathrm{ R}_{\odot}$, much larger than expectations for SN Ib progenitor stars with trace amounts of hydrogen but in agreement with previously identified SN IIb progenitor systems. The photometry of the system is also consistent with binary star models that undergo common envelope evolution, leading to a primary star hydrogen envelope mass that is mostly depleted but still seemingly in conflict with the SN Ib classification of SN 2019yvr. SN 2019yvr had signatures of strong circumstellar interaction in late-time (>150 d) spectra and imaging, and so we consider eruptive mass-loss and common envelope evolution scenarios that explain the SN Ib spectroscopic class, pre-explosion counterpart, and dense circumstellar material. We also hypothesize that the apparent inflation could be caused by a quasi-photosphere formed in an extended, low-density envelope, or circumstellar matter around the primary star.